LL-37-Induced Autophagy Contributed to the Elimination of Live Porphyromonas gingivalis Internalized in Keratinocytes - Yang, Xue; Niu, Li; Pan, Yaping; Feng, Xianghui; Liu, Jie; Guo, Yan; Pan, Chunling; Geng, Fengxue; Tang, Xiaolin (Frontiers in Cellular and Infection Microbiology, 2020)
Porphyromonas gingivalis (P. gingivalis), one of the most important pathogens of periodontitis, is closely associated with the aggravation and recurrence of periodontitis and systemic diseases. Antibacterial peptide LL-37, transcribed from the cathelicidin antimicrobial peptide (CAMP) gene, exhibits a broad spectrum of antibacterial activity and regulates the immune system. In this study, we demonstrated that LL-37 reduced the number of live P. gingivalis (ATCC 33277) in HaCaT cells in a dose-dependent manner via an antibiotic-protection assay. LL-37 promoted autophagy of HaCaT cells internalized with P. gingivalis. Inhibition of autophagy with 3-methyladenine (3-MA) weakened the inhibitory effect of LL-37 on the number of intracellular P. gingivalis. A cluster of orthologous groups (COGs) and a gene ontology (GO) functional analysis were used to individually assign 65 (10%) differentially expressed genes (DEGs) to an “Intracellular trafficking, secretion, and vesicular transport” cluster and 306 (47.08%) DEGs to metabolic processes including autophagy. Autophagy-related genes, a tripartite motif-containing 22 (TRIM22), and lysosomal-associated membrane protein 3 (LAMP3) were identified as potentially involved in LL-37-induced autophagy. Finally, bioinformatics software was utilized to construct and predict the protein–protein interaction (PPI) network of CAMP-TRIM22/LAMP3-Autophagy. The findings indicated that LL-37 can reduce the quantity of live P. gingivalis internalized in HaCaT cells by promoting autophagy in these cells. The transcriptome sequencing and analysis also revealed the potential molecular pathway of LL-37-induced autophagy.